Lapsuuden evakkomatkan monet merkitykset: Kerrontastrategiat muistelukirjoituksissa - Savolainen, Ulla (Elore, 2012)
This article focuses on the reminiscence writings of Karelian child evacuees about the evacuation journey that they experienced in their childhood. The methodological framework of this article is based on Mikhail Bakhtin’s ideas of the dialogicality of the language and the genre’s twofold nature. The research method is based on narratology and it consists of the analysis of the temporal levels of narration and writers’ positions. The evacuation journey is described in the writings as a concrete transition between places, an ongoing personal process, a metaphor for eternal homelessness and a central borderline that divides life into times before and after the evacuation. The reminiscences of the evacuation journey manifest three recurrent narrative strategies, which are 1) the fact and event oriented narrative strategy, 2) the self-reflective narrative strategy, and 3) the literary narrative strategy. Narrative strategies constitute the practice of the writers, which they use in order to compile their writings. The concept of narrative strategies enables us to understand the heterogeneity and genericality of the reminiscence writings without simplifying them too much. This article focuses on the reminiscence writings of Karelian child evacuees about the evacuation journey that they experienced in their childhood. The methodological framework of this article is based on Mikhail Bakhtin’s ideas of the dialogicality of the language and the genre’s twofold nature. The research method is based on narratology and it consists of the analysis of the temporal levels of narration and writers’ positions. The evacuation journey is described in the writings as a concrete transition between places, an ongoing personal process, a metaphor for eternal homelessness and a central borderline that divides life into times before and after the evacuation. The reminiscences of the evacuation journey manifest three recurrent narrative strategies, which are 1) the fact and event oriented narrative strategy, 2) the self-reflective narrative strategy, and 3) the literary narrative strategy. Narrative strategies constitute the practice of the writers, which they use in order to compile their writings. The concept of narrative strategies enables us to understand the heterogeneity and genericality of the reminiscence writings without simplifying them too much.